2023
DOI: 10.3390/ijerph20116021
|View full text |Cite
|
Sign up to set email alerts
|

Depression Literacy, Associated Factors, and Correlation of Related Variables in Middle-Aged Korean Adults: A Cross-Sectional Study

Abstract: For the timely treatment and management of depression, a high level of depression literacy (DL) is needed. This study aimed to examine the level of DL and factors associated with DL among middle-aged Korean adults and to verify the relationship between DL, depression, and quality of life (QoL). This cross-sectional study included 485 participants aged 40 to 64 years recruited from five provinces in Korea. DL was measured using a 22-item questionnaire and analyzed by multiple linear regression and correlation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…MHL has a negative correlation with depression and anxiety ( 25 ). D-Lit is a variable that can lead to increased professional help-seeking and improved mental health ( 26 ). Results: a study showed that MHL played a mediating role between psychological distress and mental help-seeking intentions ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…MHL has a negative correlation with depression and anxiety ( 25 ). D-Lit is a variable that can lead to increased professional help-seeking and improved mental health ( 26 ). Results: a study showed that MHL played a mediating role between psychological distress and mental help-seeking intentions ( 27 ).…”
Section: Introductionmentioning
confidence: 99%